Maduro bonds - Mitu Gulati; Ugo Panizza (Graduate Institute of International and Development Studies, 2018)
For multiple decades, activists have sought to institute an international legal regime that limits the ability of despotic governments to borrow money and then shift those obligations onto more democratic successor governments. Our goal in this article is to raise the possibility of an alternate legal path to raising the costs of borrowing for despotic regimes. All countries have systems of domestic laws that regulate agency relationships and try to deter corruption; otherwise the domestic economy would not function. Despotic governments, we conjecture, are especially likely to engage in transactions that are legally problematic. The reason being that despotic governments, by definition, lack the support of the populace; meaning that there is a high likelihood that actions that they take on behalf of the populace can be challenged as unrepresentative and contrary to the interests of the true principals. The foregoing conditions, if one translates them into the context of an ordinary principal-agent relationship, would constitute a voidable transaction in most modern legal systems. That means that if opposition parties in countries with despotic governments today were to monitor and make public the potential problems with debt issuances by their despotic rulers under their own local laws, it would raise the cost of capital for those despots. To support our argument, we use both the concrete example of the debt issuance shenanigans of the Maduro government in Venezuela and a more general analysis of the relationship between corruption, democracy and a nation's borrowing costs.
Keywords: G15; H63; K34; O54; 330; Venezuela; Odious Debt; Sovereign Default